Price and death - Jun-ichi Itaya; Heinrich W. Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2008)
How does an artist's death impact on the price of his or her works of art? We investigate this question in an infinite-horizon dynamic general equilibrium setting. Employing the open-loop Stackelberg equilibrium concept to describe the interactive behaviour of collectors and artists, we find that the art price remains at some well-defined pseudo-competitive level as long as the artist is alive. Only when the artist unexpectedly dies, the price increases on impact. This so-called death effect varies negatively with the artist's age at death. If it is well known that an artist is ailing from some terminal illness and his or her death thus does not come as a surprise, the price of the ailing artist's work increases when the news of the ailment is divulged; the price immediately jumps to the level which will prevail at the time when the artist dies.
Keywords: D90; E31; E52; 330; art prices; durable-goods monopoly; Stackelberg equilibrium; Preisniveau; Kunstgegenstand; Dauerhaftes Konsumgut; Sterblichkeit; Künstlerische Berufe; Dynamisches Gleichgewicht; Duopol; Theorie